2007
DOI: 10.1080/03079450601105676
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the results of different test systems in the 2005 global proficiency testing schemes for infectious bursal disease virus and Newcastle disease virus antibody detection in chicken serum

Abstract: The results of global proficiency testing schemes (PTS) for serological tests to detect antibodies against infectious bursal disease virus (IBDV) and Newcastle disease virus (NDV) in chicken serum, in which 125 and 120 laboratories, respectively, participated from Africa, Asia, Europe, Central and South America, were used to analyse the performances of different antibody test systems such as virus neutralization tests, haemagglutination inhibition tests, enzyme-linked immunosorbent assays and agar gel precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…The level of ND virus antibodies in serum samples were determined using the HI test as described by OIE [ 5 ]. The HI test has 98 % specificity and 69–98 % sensitivity [ 19 ]. HI titration was made to determine the right HI concentration via 2-fold serial dilution of 25 μl sera in 25 μl PBS followed by 25 μl loading of viral antigen per well.…”
Section: Methodsmentioning
confidence: 99%
“…The level of ND virus antibodies in serum samples were determined using the HI test as described by OIE [ 5 ]. The HI test has 98 % specificity and 69–98 % sensitivity [ 19 ]. HI titration was made to determine the right HI concentration via 2-fold serial dilution of 25 μl sera in 25 μl PBS followed by 25 μl loading of viral antigen per well.…”
Section: Methodsmentioning
confidence: 99%
“…Since HI is commonly used in NDV antibody diagnosis its performance has rarely been questioned. However, studies have shown that the variation between the quantitative test results of different laboratories using the NDV HI test was higher (about double) compared with the variation within commercial ELISA systems (de Wit et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, serological tests such as ELISA and HI are often relied upon for the laboratory diagnosis of ND or surveys to estimate serological prevalence, indirectly through the detection of antibodies (target condition) produced following infection by ND virus (NDV). However, these tests have limitations due to uncertainty regarding their diagnostic accuracy, as well as, lack of reproducibility under different laboratory conditions (Beard and Wilkes, 1985;Schelling et al, 1999;de Wit et al, 2007). For instance, NDV has been reported to show some degree of cross-reactivity in HI tests with several of the other avian paramyxovirus serotypes, especially APMV-3 psittacine isolates, using polyclonal antisera (Alexander et al, 1983;Lipkind and Shihmanter, 1986;Adair et al, 1989).…”
mentioning
confidence: 99%
“…The result of antibody titer obtained in monovalent vaccines Winterfield strain for us is concordant of the find by Nishizawa M, et al [9] the vaccine strain induced high IBD antibody titer. De Witt JJ, et al [10] showing the results of global proficiency testing schemes (PTS) for serological tests to detect antibodies against IBDV in chicken serum, in which 125 laboratories participated from Africa, Asia, Europe, Central and South America using: virus neutralization (VN) enzyme-linked immunosorbent assays (ELISA) and agar gel precipitation (AGP). All laboratories were asked to carry out their routine diagnostic tests for the detection of IBDV antibodies as usual.…”
Section: Discussionmentioning
confidence: 99%